Negotiating the Afterlife of Apartheid in South African townships: A Post-Apartheid Ethnographic Study of NGO Spaces and Their Role Among Black Women in Kayamandi - Mdunyelwa, Charisma Nozuko (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.